2008
DOI: 10.1177/1363460708089424
|View full text |Cite
|
Sign up to set email alerts
|

Compensated Sex and Sexual Risk: Sexual, Social and Economic Interactions between Homosexually- and Heterosexually-Identified Men of Low Income in Two Cities of Peru

Abstract: This study describes the complex dynamics of the sexual, economic and social interactions between a group of feminized homosexual men and men who have sex with men and self-identify as heterosexual ('mostaceros'), in lower-income peripheral urban areas of Lima and Trujillo, Peru. The study examined sexual risk between these two groups of men, and the significance of the economic exchanges involved in their sexual interactions. Using a Grounded Theory approach, 23 individual interviews and 7 focus groups were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…In a study about compensated sex and sexual risk among MSM in Peru, it was similarly found that self-identified homosexual men paid or gave gifts in exchange for company or sexual favors, whereas heterosexual men looked for things such as money or goods in a cycle of compensated sex dynamics. (6) The distribution of sexual positions with the past three partners revealed that only 8.2% of money-motivated MSM did not have anal sexual intercourse, which was significantly lower than it was among affection-motivated MSM (39.3%). This figure suggests that money-motivated MSM were more willing to accept anal sex with new male partners.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In a study about compensated sex and sexual risk among MSM in Peru, it was similarly found that self-identified homosexual men paid or gave gifts in exchange for company or sexual favors, whereas heterosexual men looked for things such as money or goods in a cycle of compensated sex dynamics. (6) The distribution of sexual positions with the past three partners revealed that only 8.2% of money-motivated MSM did not have anal sexual intercourse, which was significantly lower than it was among affection-motivated MSM (39.3%). This figure suggests that money-motivated MSM were more willing to accept anal sex with new male partners.…”
Section: Discussionmentioning
confidence: 90%
“…(6-10) Condom negotiation and condom use with several different sexual partners might be more difficult. Thus, although the likelihood of condom use in transactional anal sex was higher than that in affectionate sex in some studies as noted above, a few other studies still documented lower proportions of consistent condom use during anal sex in this group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma against people with HIV inhibits disclosure of HIV infection to sex partners and deters initiation of condom use or other safer sex practices that might suggest a person has HIV 9 29. Poverty and socioeconomic marginalisation of MSM leads many to engage in compensated sex for economic survival 30. A high baseline prevalence of STIs heightens the risk for the continued spread of HIV and STIs in the community 31.…”
Section: Discussionmentioning
confidence: 99%
“…The focus tends to be on gender identity (Wilton 1997;Holland et al 1998), heterosexuals' or gay/lesbian/bisexual people's understanding of their 'sexual identity' -and how this affects their sexual risk perceptions and practices (see Moore and Rosenthal 1992;Breakwell and Millward 1997;Fernández-Dávila et al 2008). Identity becomes conceptualised as comprising distinct elements, rather than as woven together into a broader sense of self.…”
Section: Identity Constructionmentioning
confidence: 99%